Success rate of repeated fine needle aspiration biopsy of clinically suspicious thyroid nodules - Nagarajah, J.; Farahati, J.; Görges, R.; Grabellus, F.; Bockisch, A.; Sheu-Grabellus, S.-Y. (Nuklearmedizin - NuclearMedicine, 2012)
In this study we evaluated the success rate of double fine needle aspiration biopsy (FNAB) of clinically suspicious thyroid nodules in one session. Aim: The success rate of FNAB in clinical setting is quite low. There were several attempts made to improve the success rate of this method. It is anticipated that a double FNAB in one session would increase the success rate of FNAB. Patients, methods: 176 consecutive patients (130 women, 46 men; mean age 56 years ± 11) with at least one clinically suspicious nodule were included in this study. Each individual nodule was biopsied twice (20G- and 21G-needle). In 33 patients, two suspicious nodules were biopsied, accounting for a total of 209 biopsied thyroid nodules. To evaluate the success rate the number of cell formations and the total number of cells in each cell formation were counted. Results: The biopsy with the 20G needle provided in mean 40 cell cluster with a mean of 830 cells niedwhereas the 21G needle provided in mean 41 cell cluster with a mean of 1010 cells. With the 20G needle the success rate was 73%, with the 21G needle 78% and the combination of the both biopsies provided a success rate of 87% (p = 0.01). Based on the number of cell formations and the total number of cells, the difference between the two needle sizes was not significant (p = 0.5 for cell formations and p = 0.9 for the total number of cells, respectively). Conclusion: A double FNAB of suspicious thyroid nodules in one session provides a higher success rate, and a 21G needle is sufficient enough.
Keywords: Fine needle aspiration biopsy; repeated biopsy; suspicious thyroid nodules